Clean burning do gás natural e seus efeitos na redução de custos do transporte marítimo - Silva, Raul Garcia da (2019)
The need for seaborne transportation will increase significantly in the years to come. At the same time, the fuel oil price is increasing, stricter emission requirements are coming into force, and the public is becoming more concerned about the environmental footprint of shipping. As a result, the industry is investigating alternative fuels for shipping. Liquefied Natural Gas (LNG) is an attractive option since it reduces the emissions set by IMO, and is expected to be cheaper than fuel oil in the future because of the large world reserves of natural gas. The objective of this work is to demonstrate, through an investigation, based on aspects of maintenance and reliability of large marine engines, through the database available in the OREDA (Offshore and Onshore Reliability Data), which exists behind the requirements of the IMO, also a significant financial gain for shipowners and operators, provided by the increased availability of marine engines due to the Clean Burning of natural gas in naval propulsion systems. An economic analysis, will show the financial gain coming with the postponement of maintenance, provided by the increased availability. Natural gas, as propulsion fuel, will provide better price offers and therefore a cost reduction for the maritime freight takers.